Degradable polyesteramide random copolymer and preparation method thereof
By prepolymerizing and polycondensing the cyclic amide with polyester monomer under the protection of nitrogen or inert gas, a random copolymer of degradable polyester amide with excellent tensile strength and elongation of break is prepared, solving the traditional high The problem of difficult degradation of molecular materials and insufficient performance achieves the environmental friendliness and high performance of the materials.
Patent Information
- Application Number
- CN202411477273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional polymer materials are difficult to degrade, resulting in environmental pollution, and existing degradable materials have shortcomings in mechanical properties and flexibility, which limits their application scope.
Using a random copolymer of degradable polyester amide and its preparation method, the cyclic amide monomer, polyester monomer, deionized water, prepolymerization catalyst and polycondensation catalyst are mixed under the protection of nitrogen or inert gas. Polymerization is then condensed under negative pressure to obtain a random copolymer of polyesteramide with good chemical stability, excellent tensile strength and elongation of break.
It realizes the environmental friendliness and high performance of the material, reduces production costs, simplifies the process flow, and improves the chemical stability, thermal performance and mechanical properties of the material, solving the environmental pollution problem of traditional polyamide materials.
Smart Images

Figure CN119192565A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a biodegradable polyesteramide random copolymer and its preparation method, belonging to the field of polymer synthesis chemistry technology. Background Technology
[0002] In recent years, polymer materials have been widely used in all aspects of society and life due to their excellent thermodynamic properties, processing performance, high thermal / chemical resistance, and steric stability. However, traditional polymer materials have drawbacks such as being difficult to degrade and causing serious environmental pollution. Biodegradable plastics are receiving increasing attention due to their environmentally friendly characteristics. Currently, relatively mature biodegradable plastics in the research of fully biodegradable polymer materials include polylactic acid, polycaprolactone, and polyglycolic acid; however, these biodegradable materials have poor mechanical properties and flexibility, which limits their promotion and application. Polyamides possess good wear resistance, oil resistance, self-lubricating properties, insulation, and mechanical properties, and have a wide range of applications. Therefore, combining polyamides with polyesters to prepare polyesteramide copolymers, which combine the biodegradability of polyesters with the mechanical properties of polyamides, is a very attractive approach for developing novel biodegradable materials.
[0003] Biodegradable polyesteramide materials are a new type of biodegradable polymer material that combines the characteristics of polyester and polyamide. It has rich structure and functionality, good mechanical and chemical properties, and excellent biodegradability and non-toxicity. It can be used in both environmentally friendly materials and biomedical materials, and has good application prospects and a wide range of applications. In addition to being used as mulch films, plastic bags, and lunch boxes, it can also be used in the biomedical field, such as bone nails and absorbable sutures.
[0004] Over the past few decades, condensation polymerization, ring-opening polymerization, and multicomponent polymerization have made good progress as the main synthetic methods for polyesteramides, but they also face many challenges. The synthesis of polyesteramides remains one of the hot topics in polymer chemistry research.
[0005] The structure and properties of polyesteramides are crucial to their applications and are of significant research importance. Polyesters exhibit good biodegradability and compatibility, but suffer from low strength. Polyamides, on the other hand, possess excellent mechanical properties, but while they offer sufficient strength, they lack toughness. Developing novel polyesteramide materials by controlling their chemical composition, thermal properties, mechanical properties, and crystallinity through structural design and catalytic synthesis is a critical issue of common concern to both academia and industry. Summary of the Invention
[0006] The purpose of this invention is to provide a biodegradable polyesteramide random copolymer and its preparation method, wherein the copolymer has good chemical stability as well as excellent tensile strength and elongation at break.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A biodegradable polyesteramide random copolymer has the following general formula:
[0009]
[0010] Where 10≤n≤300, 5≤n≤50.
[0011] The above-mentioned method for preparing biodegradable polyester amide random copolymer involves mixing cyclic amide monomers, polyester monomers, deionized water, prepolymerization catalysts, and polycondensation catalysts under nitrogen or inert gas protection, followed by a prepolymerization reaction; then, the pressure is gradually released and a vacuum is drawn, and a polycondensation reaction is carried out under negative pressure. After the reaction is completed, the copolymer is cooled, washed, and dried to obtain the biodegradable polyester amide random copolymer.
[0012] Preferably, the cyclic amide monomer is caprolactam.
[0013] Preferably, the polyester monomer is polycaprolactone or polylactide.
[0014] Preferably, the molecular weight of polycaprolactone or polylactide is 500–5000 g / mol.
[0015] Preferably, the prepolymer catalyst is nylon 66 salt, γ-aminobutyric acid, 6-amino-1-hexanoic acid, stannous octoate or 4-dimethylaminopyridine, preferably 6-amino-1-hexanoic acid.
[0016] Preferably, the polycondensation catalyst is tetrabutyl titanate, antimony trioxide, antimony glycolate, stannous octoate, or 4-dimethylaminopyridine, with tetrabutyl titanate being the most preferred.
[0017] Preferably, the mass ratio of cyclic amide monomer to deionized water is 1 to 100:1, more preferably 2 to 20:1;
[0018] The molar ratio of cyclic amide monomer to polyester monomer is 0.01 to 10:1;
[0019] The mass ratio of cyclic amide monomer to prepolymer catalyst is 100 to 10000:1;
[0020] The mass ratio of cyclic amide monomer to polycondensation catalyst is 100 to 10000:1.
[0021] Preferably, the prepolymerization reaction conditions are: pressure of 0.5-10 MPa, temperature of 140-270°C, and reaction time of 0.1-3 h.
[0022] Preferably, the conditions for the polycondensation reaction are: pressure of -500 to -10 Pa, temperature of 200 to 290 °C, and reaction time of 1 to 24 h.
[0023] The beneficial effects of the present invention are:
[0024] The prepared polymer product is biodegradable, which helps solve the environmental pollution problems faced by the traditional polyamide industry. The one-pot synthesis method avoids the cumbersome steps of multi-step methods, making the process simpler and the production cost lower. At the same time, the product has good chemical stability, low saturated water absorption, and excellent tensile strength and elongation at break. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The polyesteramide product prepared in Example 1 1 H NMR spectrum;
[0026] Figure 2 The TGA image is of the polyesteramide product prepared in Example 1;
[0027] Figure 3 The image shows the DSC diagram of the polyesteramide product prepared in Example 1.
[0028] Figure 4 The image shows the GPC diagram of the polyesteramide product prepared in Example 1. Detailed Implementation
[0029] The biodegradable polyesteramide random copolymers obtained in the following examples have the following general formula:
[0030] in,
[0031] 10≤n≤300, 5≤n≤50.
[0032] Unless otherwise specified, the experimental methods described herein are all conventional methods; unless otherwise specified, the reagents and materials described herein are all commercially available.
[0033] In the following examples, the product was measured using a 400MHz Bruker nuclear magnetic resonance instrument: 6mg of polyamide sample was placed in an NMR tube, deuterated trifluoroacetic acid was added, and the sample was measured after shaking until it was completely dissolved.
[0034] The sample decomposition temperature was measured using a TGA550 instrument. 5–10 mg of sample was weighed onto a platinum pan, and the temperature was increased at a rate of 20 °C / min under inert gas or nitrogen protection. The measured temperature range was 30–650 °C.
[0035] The sample melting temperature was determined using a DSC 250 instrument. 5–10 mg of sample was weighed onto a platinum pan. Under inert or nitrogen protection, the program was set to first heat, then cool, and finally heat again. The initial heating temperature was -50°C, and the final temperature was the temperature at which the sample degraded by 0.5% under thermogravimetric analysis. Cooling involved lowering the sample from the highest temperature back to -50°C. Melting was measured at 10°C / min. -1 It proceeds at a certain rate.
[0036] The molecular weight and molecular weight distribution index of the biodegradable polyesteramide random copolymer described in this invention were determined by gel permeation chromatography (GPC), including: an instrument (Agilent 1260), a detector (Refractive Index), and a chromatographic column (guard column + PL HFIP gel 300 × 7.5 mm in series). Operating conditions: mobile phase was hexafluoroisopropanol, flow rate was 1 mL / min, test temperature was 35 °C, and the gel permeation column was calibrated using polymethyl methacrylate (PMMA) as a standard sample. 6.0 mg of polymer sample was mixed with 1.5 mL of hexafluoroisopropanol and tested using a relative method.
[0037] The method for detecting the relative viscosity of the biodegradable polyesteramide random copolymer described in this invention is the Ubbelohde viscometer method. 0.25 g of the prepared polyesteramide copolymer sample is weighed and dissolved in a mixed solvent of phenol and 1,1,2,2-tetrachloroethane (60 / 40 w / w). The solution is prepared in a volumetric flask with c = 1 g / 100 mL, transferred to an Ubbelohde viscometer, and measured in a water bath at 25 ± 0.01 °C.
[0038] Example 1
[0039] 60g of caprolactam, 20g of polycaprolactone with a molecular weight of 1000g / mol, 6mL of deionized water, 0.24g of 6-amino-1-hexanoic acid, and 0.056mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen at room temperature for 10 minutes, the pressure was increased to 2MPa, and the reactor was heated to 250℃ and maintained at this temperature for 0.5 hours for prepolymerization. Then, the pressure was gradually released in stages until the pressure inside the reactor was completely released. A vacuum was then evacuated to -50Pa, and the reactor was heated to 260℃ and stirred for 10 hours.
[0040] After polycondensation, stirring was stopped, and the polymer product was drained into cooling water. It was then washed three times with anhydrous ethanol and dried in a 60°C oven for 12 hours to obtain a biodegradable polyesteramide random copolymer. The product had a relative viscosity of 1.69 and a saturated water absorption rate of 0.1 wt%. Figure 1 Polyesteramide product 1 The H NMR spectrum confirmed that the chemical structure was consistent with the theoretical value. (Attached) Figure 2 TGA chromatogram of polyesteramide products, T d,5%The temperature was 386℃, T d,max The temperature was 428℃, indicating that it has good thermal stability. (See attached image) Figure 3 The DSC chromatogram of the polyesteramide product shows its T... m The temperature was 171℃. The tensile strength was 37.7 MPa, and the elongation at break was 404%. Figure 4 The GPC diagram of the polyesteramide product shows that it has a narrow molecular weight distribution.
[0041] Example 2
[0042] 60g of caprolactam, 20g of polycaprolactone with a molecular weight of 1000g / mol, 5mL of deionized water, 0.06g of 4-dimethylaminopyridine, and 0.1205mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen for 10 minutes at room temperature, the pressure was increased to 2MPa, and the reactor was heated to 220℃ and maintained at this temperature for 1 hour for prepolymerization. Then, the pressure was gradually released in stages until the pressure inside the reactor was completely released. A vacuum was then evacuated to -100Pa, and the reactor was heated to 250℃ and stirred for 3 hours.
[0043] After the polycondensation is complete, stop stirring, drain the polymer product into cooling water, wash it three times with anhydrous ethanol, place it in an oven at 60°C and dry it for 12 hours to obtain a biodegradable polyesteramide random copolymer with a relative viscosity of 1.36.
[0044] Example 3
[0045] 60g of caprolactam, 10g of polycaprolactone with a molecular weight of 3000g / mol, 10mL of deionized water, 0.06g of 6-amino-1-hexanoic acid, and 0.1205mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen at room temperature for 10 minutes, the pressure was increased to 1.5 MPa, and the reactor was heated to 210°C and maintained at this temperature for 2 hours for prepolymerization. Then, the pressure was gradually released in stages until the pressure inside the reactor was completely released. A vacuum was then evacuated to -150 Pa, and the reactor was heated to 240°C. The reaction was stirred for 4 hours.
[0046] After the polycondensation is complete, stop stirring, drain the polymer product into cooling water, wash it three times with anhydrous ethanol, place it in an oven at 60°C and dry it for 12 hours to obtain a biodegradable polyesteramide random copolymer with a relative viscosity of 1.44.
[0047] Example 4
[0048] 60g of caprolactam, 15g of polycaprolactone with a molecular weight of 800g / mol, 6mL of deionized water, 0.24g of 6-amino-1-hexanoic acid, and 0.1205mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen for 10 minutes at room temperature, the pressure was increased to 4MPa, and the reactor was heated to 250℃ and maintained at this temperature for 2 hours for prepolymerization. Then, the pressure was gradually released in stages until the pressure inside the reactor was completely released. A vacuum was then evacuated to -300Pa, and the reactor was heated to 250℃ and stirred for 6 hours.
[0049] After the polycondensation is complete, stop stirring, drain the polymer product into cooling water, wash it three times with anhydrous ethanol, place it in an oven at 60°C and dry it for 12 hours to obtain a biodegradable polyesteramide random copolymer with a relative viscosity of 1.51.
[0050] Example 5
[0051] 60g of caprolactam, 20g of polycaprolactone with a molecular weight of 4000g / mol, 12mL of deionized water, 0.48g of 6-amino-1-hexanoic acid, and 0.241mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen at room temperature for 10 minutes, the pressure was increased to 3MPa, and the reactor was heated to 200℃ and maintained at this temperature for 2 hours for prepolymerization. Then, the pressure was gradually released in stages until the reactor was completely depressurized. A vacuum was then evacuated to -360Pa, and the reactor was heated to 260℃ and stirred for 8 hours.
[0052] After the polycondensation is complete, stop stirring, drain the polymer product into cooling water, wash it three times with anhydrous ethanol, place it in an oven at 60°C and dry it for 12 hours to obtain a biodegradable polyesteramide random copolymer with a relative viscosity of 1.53.
[0053] Comparative Example 1
[0054] 60g of caprolactam, 20g of caprolactone monomer, 6mL of deionized water, 0.24g of 6-amino-1-hexanoic acid, and 0.056mL of tetrabutyl titanate were sequentially added to a high-pressure reactor, which was then sealed. After purging with nitrogen at room temperature for 10 minutes, the pressure was increased to 2 MPa, and the reactor was heated to 250°C and maintained at this temperature for 0.5 hours for prepolymerization. Then, the pressure was gradually released in stages until the reactor was completely depressurized. A vacuum was then evacuated to -50 Pa, and the reactor was heated to 260°C. The reaction was stirred for 10 hours.
[0055] After polycondensation, stirring was stopped, and the polymer product was drained into cooling water. It was washed three times with anhydrous ethanol and then placed in a 60°C oven for 12 hours to obtain a biodegradable polyesteramide random copolymer. The product had a relative viscosity of 1.36, a saturated water absorption rate of 4.5 wt%, and a Tg... m The temperature is 168℃, and the temperature is Td.5% The temperature is 292℃, and the temperature is Td. max The temperature was 428℃, the tensile strength was 12.2 MPa, and the elongation at break was 7%.
[0056] Compared to Example 1, the polyesteramide copolymer obtained in Example 1 has a higher relative viscosity, indicating a larger molecular weight. Furthermore, the polyesteramide copolymer obtained in Example 1 exhibits higher thermal stability, tensile strength, and elongation at break, demonstrating that the preparation method provided in this application is superior and the prepared polymer has better performance.
[0057] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A degradable polyester amide random copolymer, characterized in that: The general formula is as follows:
2. The method for preparing the degradable polyester amide random copolymer according to claim 1, characterized in that: The method comprises the following steps: mixing cyclic amide monomer, polyester monomer, deionized water, prepolymerization catalyst and polycondensation catalyst under the protection of nitrogen or inert gas, and then performing prepolymerization reaction; then the pressure is released in stages and vacuum is drawn, and polycondensation reaction is performed under negative pressure conditions; after the reaction is completed, the method is cooled, washed and dried to obtain a degradable polyester amide random copolymer.
3. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The cyclic amide monomer is caprolactam.
4. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The polyester monomer is polycaprolactone or polylactide.
5. The method for preparing the degradable polyester amide random copolymer according to claim 4, characterized in that: The molecular weight of polycaprolactone or polylactide is 500 to 5000 g / mol.
6. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The prepolymerization catalyst is nylon 66 salt, gamma-aminobutyric acid, 6-amino-1-hexanoic acid, stannous octoate or 4-dimethylaminopyridine.
7. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The polycondensation catalyst is tetrabutyl titanate, antimony trioxide, antimony glycolate, stannous octoate or 4-dimethylaminopyridine.
8. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The mass ratio of the cyclic amide monomer to deionized water is 1 to 100:1; The molar ratio of the cyclic amide monomer to the polyester monomer is 0.01 to 10:1; The mass ratio of the cyclic amide monomer to the prepolymerization catalyst is 100 to 10000:1; The mass ratio of the cyclic amide monomer to the polycondensation catalyst is 100 to 10000:
1.
9. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The conditions for the prepolymerization reaction are: pressure of 0.5-10 MPa, temperature of 140-270° C., and reaction time of 0.1-3 h.
10. The method for preparing the degradable polyester amide random copolymer according to claim 2, characterized in that: The conditions for the polycondensation reaction are: pressure of -500 to -10 Pa, temperature of 200 to 290° C., and reaction time of 1 to 24 h.
Citation Information
Cited By
Full-bio-based degradable nylon as well as preparation method and application thereof
CN121181880A